Atherectomy in below‐the‐knee endovascular interventions: One‐year outcomes from the XLPAD registry. Issue 3 (30th November 2018) - Khalili, Houman; Jeon‐Slaughter, Haekyung; Armstrong, Ehrin J.; Baskar, Amutharani; Tejani, Ishita; Shammas, Nicolas W.; Prasad, Anand; Abu‐Fadel, Mazen; Brilakis, Emmanouil S.; Banerjee, Subhash
Abstract: Background: Use of atherectomy for the treatment of peripheral arterial disease (PAD) is increasing as an adjunctive treatment to either conventional or drug‐coated balloon angioplasty. There is limited data on atherectomy outcomes in below‐the‐knee (BTK) endovascular interventions. Methods: Data from the multicenter Excellence in Peripheral Artery Disease (XLPAD) registry (NCT01904851) were analyzed to examine predictors of atherectomy use and its associated 1‐year patency rate. We analyzed 518 BTK procedures performed between January 2005 and December 2016. Results: Overall a total of 518 BTK procedures were treated in 430 patients, and 43% of interventions used atherectomy. African American patients were less likely (13% vs 25%; |standard residual| = 3.41) to be treated with atherectomy. Use of atherectomy was lower in chronic total occlusive (CTO) lesions (48% vs 58%; P  = 0.02). There were no significant associations of baseline comorbidities, critical limb ischemia (CLI), ankle‐brachial index, number of BTK vessel run‐off, or vessel location with atherectomy use. Compared with patients without atherectomy, use of atherectomy was associated with lower incidence of repeat target limb intervention at 1 year after adjusting for age, CLI, in‐stent restenosis, heavy calcification, presence of diffuse disease, and CTO lesion traits (Hazard Ratio 0.41, 95% confidence interval 0.23‐0.72; P  < 0.01). Conclusions: Compared with no atherectomy, use of atherectomy in BTK interventions is associated with lower rates of 1‐year repeat target limb revascularization. These findings require confirmation in prospective, randomized clinical studies.